“From now on, I am Fearless” Portraying Students’ Learning Process in Creative Writing Class through their Poems - Kasprabowo, Teguh; Soepriatmadji, Liliek; Yulistiyanti, Yulistiyanti; Rahayu, Endang Yuliyani (Universitas Negeri Semarang, 2023)
This study aims to portray how students reflect their learning process in a creative writing course through their poems. Forty-seven students of an English Literature Department in a private university in Semarang participated in this study. The course mainly covered the short story and poetry writing. Poetry writing was started in the second half of the semester. In this study, the students were required to write a learning reflection to look back at the process they had been through. Employing Hanauer’s meaningful literacy concept (2012), the researchers analyzed how students reflected their learning process in their poems. It is argued that language learning should enable students to use language in a way that is more meaningful and relevant to their personal experiences. In terms of reflection, it is believed that by deliberately looking back at their learning process students can objectively evaluate, understand and make sense of their journey. This study found four major themes in the students’ reflective poems namely altered perspective, students’ struggle, increased self-assurance, and students’ future expectations. In conclusion, language learning should embrace meaningful literacy in which students should be allowed to deliver their personal and meaningful expressions, in this case by writing poetry.